Exploring teachers' roles and challenges in developing language and communication development of children with Autism spectrum disorder (ASD) - Raja Abdullah, Tengku Nornabila; Md Arshad, Syimarmasni; Abd Karim, Aishah Hanim (UNISZA, 2018)
Malaysia is one of the countries that provides education to all children including special needs children. Children with Autism Spectrum Disorder (ASD) are categorized under children with special needs because they are lacking in socializing, language and communication skills, and also involving both behavioural and cognitive problems. This study focuses on the roles of teachers and their challenges in helping autistic children to develop their language and communication skills. It is a qualitative study that uses purposive sampling method and applies semi-structured interview to collect data from six teachers who have had experiences in dealing with autistic children. Findings of this study discusses the roles of teachers such as cooperating with parents, children and other teachers; conducting observation and assessment; and managing children’s behavioural, cognitive and environmental problems. Based on the findings and discussions, it was shown that teachers who worked with ASD children possessed double crucial roles and challenges in order to support these children in their language and communication development.